Pengaruh Pengembangan Talenta dan Penugasan Pekerjaan terhadap Kinerja Karyawan di Universitas Islam Balitar (UNISBA) Blitar - Engelien Yusniar Permanasari (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this study was to examine the effect of talent development and job assignments on employee performance at Balitar Islamic University (UNISBA) Blitar. The research method is Quantitative with the type of associative research. Collecting survey data using the questionnaire method which will be distributed to research samples which contain several questions related to the indicators in this study and translated into numerical data with a Likert scale. Which of the data that has been taken will then be processed through the SPSS software. Data analysis technique using multiple linear regression test. The results of his research show: 1) there is a positive and significant influence between talent development on employee performance at Balitar Islamic University (UNISBA) Blitar. This means that if talent development increases, employee performance also increases. 2) there is a significant effect of job assignments on employee performance at Balitar Islamic University (UNISBA) Blitar. This means that the higher the job assignment, the higher the employee's performance. 3) there is an influence of talent development and job assignments on employee performance at Balitar Islamic University (UNISBA) Blitar. This means that the higher the talent development and job assignment, the higher the employee performance.